An analytical study of Abdullah bin Nuh response as modern ideologies - Ardi, Mohammad Noviani; Abdullah, Fatimah; Arief Cholil, Abdullah (Atlantis Press, 2019)
The development of modern ideologies particularly materialism, Marxism, and communism have become a matter of alarming since the early 20th century in Muslim world through colonization and imperialism. Indonesia as the one of the world’s largest Muslim population in the world did not miss on globalization of modern ideologies. Basically, Indonesia based on the Eastern and Islamic values, but after Western colonization, colonizers began to apply their ideologies in Indonesia through imperialism. As the result, clash has occurred between local ideologies and western ideologies. Abdullah bin Nuh was one of the Indonesian scholars who are concerned with the affairs of Muslim in particular his responds and critiques to modern ideologies. This study attempts at examining Abdullah bin Nuh’s views in materialism, Marxism, and communism. The approach of this study is based on textual analysis, using descriptive and analytical methods from various works of the subject under study. It seeks to discover several aspects of Abdullah bin Nuh’s thought of modern ideologies as well as Islamic thought such as the in coherent relationship of materialism, Marxism and communism, with Islamic worldview and perspective. This study concludes that Abdullah bin Nuh devoted his live to counter modern ideologies which were developed in Indonesia with presenting the understanding of those ideologies and its detrimental to social live in Indonesia. He also asserted Marxism and communism are misled ideology based on materialism which have difference culture and values with Eastern Muslim countries particularly Indonesia.